Influence of maternal age on the results of complex assisted fertilization. - Celis, Alfredo (2015)
OBJETIVE: To evaluate the influence of maternal age when assisted fertilization procedures performed highly complex. DESIGN: a retrospective observational Estádio. PATIENTS: A total of 237 cycles in women who underwent assisted fertilization procedure complex during the period March 1997 to July 1999 at the Institute of Gynecology and Fertility was evaluated. Evaluation parameters: The evaluated parámetrode included endometrial response aspirated follicles, oocytes and embryos, fertilization rate and cleavage. RESULTS: After performing the method of assisted fertilization, pregnancy occurred in 66 cycles for a total of 237, representing a rate of 27.8%. The best pregnancy rate was obtained in the group of women under 30 years (42.4%) compared to the 12.5% obtained by the group of women aged 40 or older. The fertilization rate in women under 30 was 55.1% compared to 42.6% achieved by women over 40 years. CONCLUSION: It shows a marked decline in obtaining age-related pregnancies in women over 40 who use a complex assisted fertilization procedure using autologous oocytes.